Different organic loading rates on the biogas production during the anaerobic digestion of rice straw: A pilot study. (November 2017) - Zhou, Jun; Yang, Jun; Yu, Qing; Yong, Xiaoyu; Xie, Xinxin; Zhang, Lijuan; Wei, Ping; Jia, Honghua
Highlights: Biogas production rate was 323 m 3 /t dry rice straw over the whole process. Firmicutes, Fibrobacteres, and Spirochaetes predominated in straw samples. Chloroflexi, Proteobacteria, and Planctomycetes predominated in the slurry. Hydrogenotrophic methanogens was dominated in the rice straw AD system. Abstract: The aim of this work was to investigate the mesophilic methane fermentation of rice straw at different organic loading rates (OLRs) in a 300 m 3 bioreactor. It was found that biogas production increased when the OLR was below 2.00 kg VSsubstrate /(m 3 ·d). The average volumetric biogas production reached 0.86 m 3 /(m 3 ·d) at an OLR of 2.00 kg VSsubstrate /(m 3 ·d). Biogas production rate was 323 m 3 /t dry rice straw over the whole process. The pH, chemical oxygen demand, volatile fatty acid, and NH4 + -N concentrations were all in optimal range at different OLRs. High-throughput sequencing analysis indicated that Firmicutes, Fibrobacteres, and Spirochaetes predominated in straw samples. Chloroflexi, Proteobacteria, and Planctomycetes were more abundant in the slurry. The hydrogenotrophic pathway was the main biochemical pathway of methanogenesis in the reactor. This study provides new information regarding the OLR and the differences in the spatial distribution of specific microbiota in a rice straw biogas plant.